Implementation Of Digital Marketing at PT Bipang Jangkar Abadi - Fitria, Viki Syarifatul; Wheny Khristianto; Edy Wahyudi (CV. Satria Jaya, 2024)
This research aims to describe digital marketing carried out by PT Bipang Jangkar Abadi. This research is descriptive research with a qualitative approach. Data collection techniques through interviews, observation and documentation. The data analysis used is domain analysis and taxonomic analysis. The results of this research are that PT Bipang Jangkar Abadi has implemented 3 strategies, namely planning, implementation and evaluation. PT Bipang Jangkar Abadi utilizes social media platforms as its digital marketing media such as Instagram, Facebook and TikTok as well as the Shopee and Tokopedia marketplaces. The most effective digital marketing activities are carried out through the social media platform Instagram because based on observations it shows that through creative video content and attractive discount offer strategies interactions with consumers can run effectively, this can form consumer satisfaction and build consumer loyalty significantly.